Histopathological Study of Prostatic Carcinoma in Relation to Gleason Grade, Serum PSA and Ki67 Immunomarker - Mahadev, Kanna Sandhyarani; R, Vani B; V, Srinivas Murthy (Annals of Pathology and Laboratory Medicine, 2018)
Introduction- Carcinoma of prostate (CaP) is the second most common cancer in men.Gleason’s score (GS) and pretreatment serum prostate specific antigen (sPSA) levels are important parameters in diagnosis and therapeutic decision making. Recent studies have found that GS tends to undergrade tumors and sPSA levels are not cancer specific. The present study highlights correlation between immunomarker Ki67, GS and sPSA which provides a objective method of grading tumors and helps in better prognostication of patients. Objectives- 1. To study histopathology of prostate carcinoma and its variants and assign them Gleason score as per the Gleason grading system. 2. To study Ki-67 immunoexpression in prostate carcinoma. 3. To correlate Ki-67 expression, Gleason scoring and serum prostate specific antigen levels in prostate carcinoma Methods -A retro-prospective study was done on 100 specimens of prostate carcinoma from the year 2010-2015 in Department of Pathology of ESIC Medical College and PGIMSR, Rajajinagar, Bangalore for a period of 18 months(November2013-April2015).Each case was assigned Gleason score and subjected to immunohistochemistry for Ki67 expression. Results of Ki67 expression was correlated with Gleason score and PSA levels. Results-Out of the 100 cases studied, all case were of acinar/usual adenocarcinoma-WHO type. 40 cases were moderately differentiated, 39 cases were high grade tumors and 21 cases were intermediate grade tumors. Serum PSA levels increased with increase in GS. Ki67 labelling index showed a proportionate increase with increase in GS and serum PSA which was statistically significant. Conclusion- Ki67 is a new emerging biomarker which is significantly associated with tumor grade and pretreatment PSA levels and can be used as an additive parameter or a substitution to known prognostic variables to aid in therapeutic interventions.